ON THE MINIMAL SEQUENTIAL CALCULI OF ROBINSON’S ARITHMETIC - Chubaryan, A. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
Sequential calculi of minimal Robinson’s arithmetic (with cut rule and cut- free) are defined in this paper. Equivalence of these calculi is proved.